Upaya Pencegahan Anemia pada Remaja Putri - Julaecha Julaecha (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
AbstractAnemia is a micronutrient problem that occurs throughout the world especially in developing countries which is estimated to occur in 30% of the world's population. As a result of lack of hemoglobin levels causes symptoms of lethargy, fatigue and tired quickly when doing activities that will have an impact on decreased concentration and learning achievement, and in the long run it will have an impact on the quality of human resources, where young women are the future generation of the nation which will later supports determining the next generation. The results of basic health research in 2013 anemia in adolescent girls increased to 48.9% in 2018. Data from the Health Office in Jambi City in 2017 as many as 257 adolescent girls who experienced anemia, increased to 404 people in 2018. The purpose of this community service is to provide information to adolescents about anemia and the importance of consuming blood-added tablets. The method used in this community service is lecture, question and answer discussion. This community service was held on February 13-14, 2019 at SMAN 8 Jambi City. The result of this community service is the increasing knowledge of young women about anemia and the benefits of consuming blood-added tablets.